PERAN LITIGATION RISK DALAM MEMODERASI PENGARUH LIFE CYCLE DAN LEGAL EXPERTISE TERHADAP PRUDENCE AKUNTANSI - Meisy Meisy; Christina Dwi Astuti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This research aims to analyse and get an empirical evidence on the effect of life cycle and life cycle on accounting prudence with litigation risk as moderating variable. This study adds the litigation risk variable as a moderation variable, because litigation can cause a significant decrease in value in a company and the company will bear a large burden of demands from the litigation risk.The population in this study includes 105 financial companies listed on Indonesia Stock Exchange in 2011-2021. The sample was selected using purposive sampling method. Based on the predetermined criteria, a total of 665 unbalanced samples were obtained. Multiple linear regression analysis is used as the analytical technique. Analysis result shown that partially Life Cycle has negative effect on Accounting Prudence, Legal Expertise has no significant effect on Accounting Prudence, Litigation Risk weakens the relationship of Life Cycle on Accounting Prudence, Litigation Risk does not moderate the relationship of Legal Expertise on Accounting Prudence. This research brings objectives in the analysis and finds the effect of life cycle on prudence moderated by litigation risk in the company the financial sector during the 2011-2021 period which has been listed on the IDX. The recommendation for further research is to add other indicators to measure accounting prudence such as earnings/stock return measures so that they can be used as comparison material regarding the consistency of proxy use. Further researchers are also expected to add other factors that can affect accounting prudence such as conflicts of interest, company risk, political costs, and taxes.